Poor biofilm-forming ability and long-term survival of invasive Salmonella Typhimurium ST313. Issue 5 (23rd May 2016) - Ramachandran, Girish; Aheto, Komi; Shirtliff , Mark E.; Tennant, Sharon M.
Abstract : Salmonella enterica serovar Typhimurium, an enteric pathogen that causes a self-limiting gastroenteritis, forms biofilms on different surfaces. In sub-Saharan Africa, Salmonella Typhimurium of a novel sequence type (ST) 313 was identified and produces septicemia in the absence of gastroenteritis. No animal reservoir has been identified, and it is hypothesized that transmission occurs via human to human. In this study, we show that invasive Salmonella Typhimurium ST313 strains from Mali are poor biofilm producers compared to Salmonella Typhimurium ST19 strains, which are found worldwide and are known to be associated with gastroenteritis. We evaluated biofilms using crystal violet staining, examination of the red, dry and rough morphotype, pellicle formation and a continuous flow system. One month-old Salmonella Typhimurium ST19 colonies survived in the absence of exogenous nutrients and were highly resistant to sodium hypochlorite treatment compared to Salmonella Typhimurium ST313. This study for the first time demonstrates the comparative biofilm-forming ability and long-term survival of clinical Salmonella Typhimurium ST19 and ST313 isolates. Salmonella Typhimurium ST19 strains are strong biofilm producers and can survive desiccation compared to Salmonella Typhimurium ST313 that form weak biofilms and survive poorly following desiccation. Our data suggest that like Salmonella Typhi, Salmonella Typhimurium ST313 lack mechanisms that allow it to persist in the environment. Abstract : Invasive Salmonella Typhimurium ST313 from Mali are poor biofilm formers and are more sensitive to desiccation compared to the classical gastroenteritis causing Salmonella Typhimurium ST19.